2001
DOI: 10.1002/crq.3890180406
|View full text |Cite
|
Sign up to set email alerts
|

Conflict education and special‐needs students, part two: Improving conflict competence and emotional competence

Abstract: Although special‐needs students are typified by emotional and behavioral disabilities that are critical to their conflict orientation and conflict behavior, very little work has been done to bring conflict education programs to them; even less has been done to explore the efficacy of these interventions. This article reports on the impact of conflict education training provided to thirteen upper school classes of a special‐needs population in a private school setting. Training was delivered in sessions of one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The remaining five studies reported age ranges for their participants, and these spanned the 12-to 19-year age range. Most studies' participants were either exclusively male or mostly male, two studies (Bodtker, 2001;Larson & Gerber, 1987) did not report gender proportions, and one study (LeCroy, 1988) involved exclusively female participants.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining five studies reported age ranges for their participants, and these spanned the 12-to 19-year age range. Most studies' participants were either exclusively male or mostly male, two studies (Bodtker, 2001;Larson & Gerber, 1987) did not report gender proportions, and one study (LeCroy, 1988) involved exclusively female participants.…”
Section: Participantsmentioning
confidence: 99%
“…Finally, the majority of studies that reported sample attrition rates (57%) lost no participants in the research process. Three studies did not report attrition rates (Bodtker, 2001;Etscheidt, 1991;LeCroy, 1988). Among the studies that did report a measurable attrition rate, these rates ranged from 8% in the Dangel, Deschner, and Rasp (1989) study to 38% in one of the treatment groups in the Barkley et al (2001) study.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…All treatment classrooms showed significant increases in moral reasoning ability and constructive conflict orientation. In a two-year study of the impact of a conflict education curriculum in middle and high school special-needs students (in an alternative disciplinary school), researchers found that the conflict curriculum had a significant impact on students' misconduct rates, hostile attribution, and aggressive orientation (Jones and Bodtker, 1999;Bodtker, 2001). …”
Section: Peer Mediation Research In Middle Schoolsmentioning
confidence: 99%